A Tris(hydroxymethyl)aminomethane‐Rhodamine Spirolactam Derivative as Dual Channel pH and Water Sensor and Its Application to Bio Imaging. Issue 21 (16th June 2015) - Devi, Manisha; Dhir, Abhimanew; Pradeep, Chullikkattil P.
Abstract: A rhodamine spirolactam derivative, R1, having tris(hydroxymethyl)aminomethane moiety as substituent on the spirolactam ring has been synthesized and characterized.R1 shows visual colour change and fluorescence in protic solvents and it is capable of sensing trace amounts of water present in organic solvents. In addition, R1 shows reversible ON–OFF switching in its fluorescence and absorption properties as a function of solution pH. Different from majority of the reported rhodamine spirolactam derivatives, R1 shows strong fluorescence and absorption over a wide pH range (pH 3–9) and on either side of this range, it gets converted into colourless and non‐fluorescent ring closed form. The reversible ring opening and ring closure ofR1 as a function of solution pH have been supported by spectroscopic analyses. We also demonstrate the potential use ofR1 in cell imaging as it stains selectively the nucleus of Allium cepa root tip cells and human white blood cells (WBCs) at lower concentrations. Abstract : A rhodamine spirolactam derivative, R1 has been synthesized and characterized.R1 shows visual colour change and strong fluorescence in trace amount of water in organic solvents and also over a wide pH range (pH 3–9).R1 is applicable in cell imaging of nucleus of Allium cepa root tip cells and human WBCs.